Comparison of vitamin D intake and ultraviolet light exposure in pre and postmenopausal women in the elderly pandemic period - Syahrial Syahrial; Resmiati Resmiati; Ricvan Dana Nindrea; Faiz Nur Hanum (Jurnal Gizi dan Dietetik Indonesia (Indonesian Journal of Nutrition and Dietetics), 2022)
Background: Osteoporosis is one of the degenerative diseases in the elderly which is still a priority health problem in Indonesia. There are several precautions that can be taken to prevent the occurrence of osteoporosis, one of that is vitamin D. Vitamin D can be obtained through exposure to Ultraviolet (UV) rays from the sun and from nutritional sources of food. Vitamin D can slow down the process of osteoporosis, because vitamin D is able to maintain bone health by increasing the absorption of the mineral calcium. Objectives: The purpose of this study is to see the comparison of vitamin D intake and UV exposure in pre and postmenopausal women during the pandemic.Methods: This research was an analytic study conducted with a cross sectional research design, which compares predictor variables and outcome variables that are viewed simultaneously. The study was conducted on women aged 35-65 years at the Elderly Posyandu, Padang City. Then the results of the data obtained will be analyzed using the Anova test.Results: The results showed that the percentage of menopausal respondents exposed to UV light was higher (87.5%) compared to those who were not exposed to UV light (12.5%). Then the percentage of menopausal respondents based on the consumption of Vit D < RDA was higher (52.5%) than the consumption of Vit D > RDA (47.5%).Conclusions: There was no significant difference (p<0.05) between the incidence of menopause and levels of vitamin D intake (p=0.381) and UV light exposure (p=0.462) in the elderly at the Posyandu Lansia, Padang City